Umarla Klasa . Dead Class - Wajda, Andrzej (Poland, 1976)
Donated by the Arts and Culture Program, CEU Andrzej Wajda documents the "hair-raising spectacle" of Tadeusz Kantor's most famous work “Dead Class”, which won an Obie Award for its 1979 performance at La Mama. Here, in the crucible of Krakow's Krzysztofory Gallery, where the work premiered, Kantor incites and conducts the psychosis at the core of personal and collective memory – memory shaped in this case by the traumas of two World Wars, the Holocaust, and the eradication of the Jewish part of Polish culture – and he pushes his avant-garde poetic into its final phase, the "Theatre of Death."